Takotsubo cardiomyopathy post liver transplantation - Vachiat, Ahmed (Cardiovasc J Afr, 2016)
A patient with end-stage liver disease developed stressinduced Takotsubo cardiomyopathy post liver transplantation, with haemodynamic instability requiring a left ventricular assist device. We discuss the diagnosis and management of this condition.